2019
DOI: 10.1042/ebc20180071
|View full text |Cite
|
Sign up to set email alerts
|

Basement membrane collagens and disease mechanisms

Abstract: Basement membranes (BMs) are specialised extracellular matrix (ECM) structures and collagens are a key component required for BM function. While collagen IV is the major BM collagen, collagens VI, VII, XV, XVII and XVIII are also present. Mutations in these collagens cause rare multi-systemic diseases but these collagens have also been associated with major common diseases including stroke. Developing treatments for these conditions will require a collective effort to increase our fundamental understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 158 publications
0
58
0
Order By: Relevance
“…Overall, this study identified significantly enhanced immunosignals for collagen IV and fibronectin following focal cerebral ischemia in mice, rats, sheep, and in human stroke tissue. Derived from the observed close regional association of collagen IV and fibronectin -and considering their primary locations with reference to the basement membrane and the adjoined ECM Singh et al, 2010;Gatseva et al, 2019) -this study provides robust evidence for an ischemia-induced critical affection of the NMZ. Given the fact of the assumed highly dynamic situation at this site, different patterns of the collagen IV and especially the fibronectin immunosignal would have been expected over time.…”
Section: Histomorphological Characterization Of Collagen IV and Fibromentioning
confidence: 60%
See 2 more Smart Citations
“…Overall, this study identified significantly enhanced immunosignals for collagen IV and fibronectin following focal cerebral ischemia in mice, rats, sheep, and in human stroke tissue. Derived from the observed close regional association of collagen IV and fibronectin -and considering their primary locations with reference to the basement membrane and the adjoined ECM Singh et al, 2010;Gatseva et al, 2019) -this study provides robust evidence for an ischemia-induced critical affection of the NMZ. Given the fact of the assumed highly dynamic situation at this site, different patterns of the collagen IV and especially the fibronectin immunosignal would have been expected over time.…”
Section: Histomorphological Characterization Of Collagen IV and Fibromentioning
confidence: 60%
“…Using multiple immunofluorescence approaches to tissues affected by different durations of focal cerebral ischemia, a spatio-temporal characterization of collagen IV as the major part of the basement membrane (Thomsen et al, 2017;Gatseva et al, 2019), and fibronectin as a major component of the ECM (Singh et al, 2010;Mezzenga and Mitsi, 2019) was performed. To consider the phenomenon of a translational roadblock in the field of stroke research that was at least partially related to artificial models (Young et al, 2007;Endres et al, 2008), efforts have been made to use different animal models with individual strengths and weaknesses (Durukan and Tatlisumak, 2007) as well as different species for this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, I have summarized our precarious knowledge of the mechanisms generating BM diversity and increased thickness or aggregate-like deposition in atypical structures. Importantly, changes in BM thickness are associated with diseases that affect the blood brain barrier, kidneys, cornea or retina (Chew and Lennon, 2018;Gatseva et al, 2019;Pozzi et al, 2017;Sekiguchi and Yamada, 2018). Furthermore, thick matrix deposits are seen in fibrotic conditions, where the expression of matrix proteins is upregulated, but the mechanisms that make that excess matrix form aberrant structures are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…DyProQ could also be used to study the biosynthesis of other collagens, e.g. collagen-II and collagen-XI in Stickler syndrome, collagen-III and collagen-V in the Ehlers Danlos syndrome, collagen-VI in Ullrich congenital muscular dystrophy and Bethlem myopathy, collagen-VII in epidermolysis bullosa, and collagen-IV in sporadic cerebral small vessel disease 46 and major common diseases including stroke (reviewed by 47 ). DyProQ has wide-ranging applications in studies of other proteins that are expressed at levels too low to be detected by fluorescent protein tagging of the endogenous protein.…”
Section: Discussionmentioning
confidence: 99%